Fluxo de capital e qualidade institucional das economias emergentes - Katia Rocha; Ajax Reynaldo Bello Moreira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– This study examines the relationship between institutional quality and capital flows to emerging economies. Such index correspond to a structural long-run determinant to capital flows and is actually little discussed in the literature. The 13 economies analyzed between 2000-2014 accounted for over 70% of the JPMorgan Emerging Markets Bond Index Global in September 2016. The model specification has the merit to measure the direct and indirect effects of the variables considered exogenous in domestic fundamentals which according to our knowledge is an innovative approach. The main results suggest that improved institutional quality of the emerging economy is closely linked to increased capital inflow, particularly to foreign direct investment. A typical increase in institutional quality could compensate emerging economies for an adverse international liquidity or global risk aversion shocks.
Keywords: F21; F36; G38; C23; 330; capital flow; emerging economies; governance and institutional qualities